2017
DOI: 10.1080/1061186x.2017.1365874
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in targeted delivery of tissue plasminogen activator for enhanced thrombolysis in ischaemic stroke

Abstract: Tissue plasminogen activator (tPA) is the only FDA approved medical treatment for the ischaemic stroke. However, it associates with some inevitable limitations, including: short therapeutic window, extremely short half-life and low penetration in large clots. Systemic administration may lead to complications such as haemorrhagic conversion in the brain and relapse in the form of re-occlusion. Furthermore, ultrasound has been utilised in combination with contrast agents, echogenic liposome, microspheres or nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 125 publications
0
32
0
Order By: Relevance
“…As recently reviewed, 86,87 nanotechnology has the potential to offer innovative solutions, which address the shortfalls of rt-PA. For example, dramatic prolongation of rt-PA half-life has been achieved by encapsulation of rt-PA in PEG-modified liposomes, 88 in zinc-stabilized gelatin nanoparticles, 89 in the porous structure of soft discoidal polymeric nanoconstructs (tPA-DPNs) 90 or by shielding rt-PA from plasma inactivation by complexing with albumin, then recovering its local thrombolytic activity by release-triggers such as heparin or thrombin. 86,91 Improved clot penetration, leading to better thrombolysis and subsequent dose reduction was achieved by rt-PA encapsulation in biocompatible polymers such as synthetic polylactic-co-glycolytic acid combined with natural polysaccharides like chitosan.…”
Section: Clot Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently reviewed, 86,87 nanotechnology has the potential to offer innovative solutions, which address the shortfalls of rt-PA. For example, dramatic prolongation of rt-PA half-life has been achieved by encapsulation of rt-PA in PEG-modified liposomes, 88 in zinc-stabilized gelatin nanoparticles, 89 in the porous structure of soft discoidal polymeric nanoconstructs (tPA-DPNs) 90 or by shielding rt-PA from plasma inactivation by complexing with albumin, then recovering its local thrombolytic activity by release-triggers such as heparin or thrombin. 86,91 Improved clot penetration, leading to better thrombolysis and subsequent dose reduction was achieved by rt-PA encapsulation in biocompatible polymers such as synthetic polylactic-co-glycolytic acid combined with natural polysaccharides like chitosan.…”
Section: Clot Removalmentioning
confidence: 99%
“…92,93 The use of certain nanoparticle shapes, such as iron oxide nanocubes 78 and elongated nanotubes derived from tobacco mosaic virus (TMV), can increase rt-PA targeting to vascular thrombi 94 and potentially mitigate fatal side effects of rt-PA. It has been demonstrated that rt-PA-conjugated TMV nanorods reduced the risk of bleeding post rt-PA administration compared with free rt-PA in a Rose Bengal model of mouse carotid artery thrombosis 95 (for extensive recent reviews on the latter refer to Liu et al 86 and Xamalu et al 87 ). More recent work has made use of cyclic arginine-glycine-aspartic acid coating to enable selective targeting of t-PA-loaded PEGylated liposomes to activated platelets, achieving considerably higher in vitro thrombolysis following liposomal membrane fusion and enhanced t-PA release.…”
Section: Clot Removalmentioning
confidence: 99%
“…Similarly, magnetically responsive liposomes, microbubbles, and microparticles and nanoparticles can be driven to accumulate at the thrombus site using external magnetic fields. This topic has been reviewed in the past with focus on targeting and stage of development . In this review, we highlight engineered microparticle and nanoparticle PA carriers with special attention to particles externally actuated by ultrasound or magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…This topic has been reviewed in the past with focus on targeting 37 and stage of development. 38 In this review, we highlight engineered microparticle and nanoparticle PA carriers with special attention to particles externally actuated by ultrasound or magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] With regard to thromboembolic disease, substantial efforts have gone into establishing novel delivery systems to optimize thrombolytic agents delivery. [23][24][25][26][27] Some smart delivery systems for controlled release of thrombolytic agents, as stimulated by external signals, have high potential to reduce the risk of systemic bleeding complications and to provide a more effective and safer drug thrombolysis. In this…”
mentioning
confidence: 99%